Case report: acute clinical presentation and neonatal management of primary hyperparathyroidism due to a novel CaSR mutation - Manuela Capozza; Iolanda Chinellato; Vito Guarnieri; Natascia Di lorgi; Maria Accadia; Cristina Traggiai; Girolamo Mattioli; Antonio Di Mauro; Nicola Laforgia (BMC, 2018)
Abstract Background Neonatal severe primary hyperparathyroidism (NSHPT) is a rare autosomal recessive disorder of calcium homeostasis, characterized by striking hyperparathyroidism, marked hypercalcemia and hyperparathyroid bone disease. We report the case of a newborn with a novel homozygous mutation of the CaSR, treated by successful subtotal parathyroidectomy, who had an acute presentation of the disease, i.e. out-of hospital cardiorespiratory arrest. . Case presentation A 8-day-old female newborn was admitted to the NICU of University of Bari "Aldo Moro" (Italy) after a cardiorespiratory arrest occurred at home. Severe hypercalcemia was found and different drug therapies were employed (Furosemide, Cinacalcet and bisphosphonate), as well as hyperhydration, until subtotal parathyroidectomy, was performed at day 32. Our patient's mutation was never described before so that a strict and individualized long-term follow-up was started. Conclusions This case of NSHPT suggests that a near-miss event, labelled as a possible case of SIDS, could also be due to severe hypercalcemia and evidentiates the difficulties of the neonatal management of NSHPT. Furthermore, the identification of the specific CaSR mutation provides the substrate for prenatal diagnosis.